The Role of Environmental Factors on Grammatical Development in French–English Bilinguals Attending a Dual Language Programme in France - Cathy Cohen; Erin Quirk (Languages)
This mixed methods study explores the effects of cumulative exposure, age of onset of acquisition (AO), parent proficiency and richness of the language environment on the grammatical development in French and English of 49 French–English bilingual children who were acquiring the languages either simultaneously (2L1) or successively (cL2). Participants (24 girls) were in 1st grade (M = 6;4, n = 20) or 5th grade (M = 10;4, n = 29), attending a state school in France, in a French–English bilingual programme. Production data come from a narrative task in each language. Parent questionnaires were used to explore environmental factors. Results show, first, that children’s age and parent proficiency were positive predictors of grammatical accuracy in English, while in French only cumulative exposure was a positive predictor. Secondly, exposure showed a stronger relationship with grammatical accuracy in cL2 children; however, only in French, the language in which children made more errors overall. Finally, we found that both 2L1 and cL2 children made gender errors, an early-acquired structure in French. A qualitative analysis of errors with gender highlights, first, the importance of language output for grammatical development, even for children receiving substantial language input and, second, the role of home factors which play a more important role than community language use in shaping grammatical development. This study underscores the complex, interconnected nature of experiential effects on bilingual grammatical development in each language.